Low sensitivity of chromogranin A in the diagnosis of insulinoma: a single-center study - Marina Y. Yukina; Ekaterina A. Troshina; Nurana F. Nuralieva; Olga Y. Rebrova; Larisa V. Nikankina; Natalia G. Mokrysheva (Alʹmanah Kliničeskoj Mediciny, 2024)
Background: Insulinoma is a neuroendocrine tumor (NET), with its main clinical manifestation being the hypoglycemic syndrome. The symptoms of hypoglycemia are nonspecific, and therefore, in most cases, the diagnosis is made untimely. The Russian clinical guidelines for the diagnosis and treatment of NET suggest as a diagnostic test that the universal circulating marker of all NET, chromogranin A (CgA) be determined. However, the literature data on the sensitivity of CgA in the diagnosis of insulinoma are contradictory.